Current status, trends, and predictions in the burden of gallbladder and biliary tract cancer in China from 1990 to 2019. Issue 14 (20th July 2022) - Chen, Shimin; Han, Ke; Song, Yang; Liu, Shaohua; Li, Xuehang; Wang, Shengshu; Li, Haowei; Li, Rongrong; Wang, Jianhua; He, Yao; Liu, Miao
Abstract: Background: Gallbladder and biliary tract cancer (GBTC) has greatly damaged the health of patients and is accompanied by a dismal prognosis. The worldwide distribution of GBTC shows extensive variance and the updated data in China is lacking. This study was to determine the current status, trends, and predictions in the burden of GBTC over the past 30 years in China. Methods: This was a descriptive, epidemiological, secondary analysis of the Global Burden of Disease, Injuries, and Risk Factor Study 2019 data. Data including incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of GBTC in China by year, age, and sex were assessed. Joinpoint regression analysis was conducted to evaluate trends of disease burden due to GBTC from 1990 to 2019. Nordpred age-period-cohort analysis was applied for the projection of mortality and incidence due to GBTC from 2019 to 2044. Results: Nationally, there were 38, 634 (95% uncertainty interval [UI]: 27, 350–46, 512) new cases and 47, 278 (95% UI: 32, 889–57, 229) patients due to GBTC, causing 34, 462 (95% UI: 25, 220–41, 231) deaths, and 763, 584 (95% UI: 566, 755–920, 493) DALYs in 2019. Both cases and rates of burden owing to GBTC were heavier among males and at old age. From 1990 to 2019, the age-standardized rates of incidence, prevalence, mortality, and DALYs of GBTC generally increased from 1990 to 2019, with average annual percentage change at 0.8% (95% confidential interval [CI]: 0.6–1.0%), 1.3% (95% CI: 1.1–1.5%), 0.4% (95% CI: 0.2–0.6%), and 0.2% (95% CI: 0.1–0.4%), respectively. Even though the age-standardized incidence rate and age-standardized mortality rate in both sexes were predicted to decline gradually from 2019 to 2044, the number of new cases and deaths were expected to grow steadily. Conclusions: GBTC is becoming a major health burden in China, particularly among males and older individuals. Given the aging population and increasing burden, effective strategies and measurements are urged to prevent or reduce the number of new cases and deaths of GBTC.